2010
DOI: 10.1177/1010539509355599
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Tobacco Smoking in Sri Lanka

Abstract: Smoking is common among Sri Lankan males and is associated with lower education, income, and middle age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
6
34
1
Order By: Relevance
“…Our finding is in concordance with other Chinese studies [3,22]. In this study, the prevalence of smoking among men was greater than the prevalence rate observed in 2010 China Global Adults Tobacco Survey (GATS, 56.1%) [23] and other Asian people [24]. As a result of such high smoking prevalence rate, 97.84% of the total economic cost of smoking was borne by men in the sampled communities, which was much higher than the findings from an Indian study (87%) [25], indicating that smoking is a serious public health concern especially for men in rural south-west China, and presenting great challenge to local policymakers to implement the tobacco control policies to reduce tobacco use.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding is in concordance with other Chinese studies [3,22]. In this study, the prevalence of smoking among men was greater than the prevalence rate observed in 2010 China Global Adults Tobacco Survey (GATS, 56.1%) [23] and other Asian people [24]. As a result of such high smoking prevalence rate, 97.84% of the total economic cost of smoking was borne by men in the sampled communities, which was much higher than the findings from an Indian study (87%) [25], indicating that smoking is a serious public health concern especially for men in rural south-west China, and presenting great challenge to local policymakers to implement the tobacco control policies to reduce tobacco use.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of hospitalization due to diabetes mellitus (DM), hypertension and ischaemic heart disease is increasing in Sri Lanka 3 . One in four adults over 20 years has hypertension with a prevalence of 28.4% 4 . Meanwhile, the number of patients admitted to hospitals due to hypertension was 469.8 cases per 100,000 population and number of deaths was 2.9 per 100,000 population in Sri Lanka in the year 2007 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The rate of smoking among controls was taken as 38% based on smoking prevalence in Sri Lanka [8]. Odds ratio associated with the exposure (smoking) was taken as 2.7 [9].…”
Section: Methodsmentioning
confidence: 99%